Temperature sheets and aspect sensitive radar echoes - H. Luce; M. Crochet; F. Dalaudier (Annales Geophysicae, 2001)
here have been years of discussion and controversy about the existence of very thin and stable temperature sheets and their relationship to the VHF radar aspect sensitivity. It is only recently that very high-resolution in situ temperature observations have brought credence to the reality and ubiquity of these structures in the free atmosphere and to their contribution to radar echo enhancements along the vertical. Indeed, measurements with very high-resolution sensors are still extremely rare and rather difficult to obtain outside of the planetary boundary layer. They have only been carried out up to the lower stratosphere by Service d’A´ eronomie (CNRS, France) for about 10 years. The controversy also persisted due to the volume resolution of the (Mesosphere)-Stratosphere-Troposphere VHF radars which is coarse with respect to sheet thickness, although widely sufficient for meteorological or mesoscale investigations. The contribution within the range gate of many of these structures, which are advected by the wind, and decay and grow at different instants and could be distorted either by internal gravity waves or turbulence fields, could lead to radar echoes with statistical properties similar to those produced by anisotropic turbulence. Some questions thus remain regarding the manner in which temperature sheets contribute to VHF radar echoes. In particular, the zenithal and azimuthal angular dependence of the echo power may not only be produced by diffuse reflection on stable distorted or corrugated sheets, but also by extra contributions from anisotropic turbulence occurring in the stratified atmosphere. Thus, for several years, efforts have been put forth to improve the radar height resolution in order to better describe thin structures. Frequency interferometric techniques are widely used and have been recently further developed with the implementation of high-resolution data processings. We begin by reviewing briefly some characteristics of the ST radar echoes with a particular emphasis on recent works. Their possible coupling with stable sheets is then presented and their known characteristics are described with some hypotheses concerning their generation mechanisms. Finally, measurement campaigns that took recently place or will be carried out in the near future for improving our knowledge of these small-scale structures are presented briefly. Key words. Meteorology and atmospheric dynamics (turbulence; instruments and techniques) – Radio Science (remote sensing)